Soil carbon pool under organic and conventional crop production system of semi arid tropics (Bangladesh Journal of Botany, 2021)
Regardless of land use, the results indicated significant differences in all the studied parameters. Total % SOC ranged from 0.52 to 0.72 for conventional farm samples (mean 0.62%) and 0.63 to 1.59 for the organic samples (mean 1.19). Bulk density (g/cc) ranged from 0.43 to 0.81 (mean 0. 62) for conventional and 0.17 to 0.28 (mean 0.20) organic farm soils. Organic manures increased microbial biomass carbon by 117% and dissolved organic carbon (DOC) concentration by 181% over conventional farming. The results suggested that organic matter is better protected in organic soils and are consequently less vulnerable to mineralization.